QOLP-41. ASSESSING CAREGIVERS' OF PATIENTS WITH PRIMARY BRAIN TUMORS EXPERIENCES WITH AND NEEDS RELATED TO SEIZURE MANAGEMENT. (11th November 2019) - Warren, Paula; Ejem, Deborah; Taylor, Richard; Edwards, Rebecca; Dionne-Odom, James; Nabors, Louis; Bakitas, Marie
Abstract: Family caregivers of persons with primary brain tumors report high levels of distress. Information is limited, however, regarding family caregivers' experiences and needs concerning the risk and management of seizures in this population. In this qualitative descriptive study, we conducted one-on-one interviews to describe the experiences of family caregivers' of persons with primary brain tumors who have had and who have not yet had a seizure. We sought information on how they coped with this issue and what information they needed regarding management of out-of-the-hospital seizures. We conducted 15 interviews using study-specific interview protocols; 10 caregivers with seizure experience and 5 caregivers without seizure experience. Caregivers were, on average, 52 years old, predominately white (93.3%), college graduates (66.7%), and were employed full-time (53.3%). The relationship between caregiver and care recipient was spouse (46.7%), other family member (46.7%), and friend (6.6%). Most caregivers provided care everyday (46.7%) and for more than 8 hours per day (33.3%). Themes emerged around three major domains: 1) caregiver challenges regarding seizures, 2) desired resources/information about seizures, and 3) timing of delivery of these resources. Caregivers often reported being fearful of seizures and the majority (93%) expressed difficulty with knowing when to call EMS. In terms of desired resources, opinions were split between preferring written materials versus online resources with most participants (87%) stating that videos or graphics detailing seizures would be helpful. In terms of delivery timing, most (66.7%) thought that training should come after diagnosis versus at the time of diagnosis citing reasons such as too much other information to absorb and overall inability to focus. Future studies will use this information to develop and pilot a seizure-focused supportive caregiver intervention that is tailored and caregiver-directed and that can be incorporated into standard neuro-oncology clinical practice.